Long Non-coding RNA MIAT Knockdown Prevents the Formation of Intracranial Aneurysm by Downregulating ENC1 via MYC - Li, Xinguo; Zhao, Hang; Liu, Jihui; Tong, Jing (Frontiers in Physiology, 2021)
Intracranial aneurysm (IA) is vascular enlargement occurred on the wall of cerebral vessels and can result in fatal subarachnoid hemorrhage when ruptured. Recent studies have supported the important role of long non-coding RNAs (lncRNAs) in IA treatment. This study identified functional significance of lncRNA myocardial infarction associated transcript (MIAT) in IA. MIAT and ectodermal-neural cortex 1 (ENC1) expression was detected by RT-qPCR. CCK-8 assay flow cytometry were conducted to detect cell viability and apoptosis of endothelial cells in IA. The interaction among MIAT, ENC1 and myelocytomatosis oncogene (MYC) was analyzed by RNA pull down, RNA immunoprecipitation assay, chromatin immunoprecipitation assay and dual luciferase reporter assay. IA was induced by ligating the left carotid artery and the bilateral posterior branch of the renal artery in rats for studying the role of MIAT and ENC1 in vivo. MIAT and ENC1 were upregulated in IA. Endothelial cells in IA presented a decreased cell viability and an increased apoptotic rate. MIAT could regulate the expression of ENC1, and MYC could bind to the promoter region of ENC1. High expression of MIAT increased endothelial cell apoptosis and vascular endothelial injury, while MIAT knockdown was identified to reduce the risk of IA both in vitro and in vivo through regulating ENC1. To sum up, MIAT silencing is preventive for IA occurrence by decreasing the MYC-mediated ENC1 expression, which represents a novel therapeutic target for IA.